y=2z

Rewrite the equation as 2z=y.

2z=y

Divide each term in 2z=y by 2.

2z2=y2

Cancel the common factor of 2.

Cancel the common factor.

2z2=y2

Divide z by 1.

z=y2

z=y2

z=y2

To remove the radical on the left side of the equation, square both sides of the equation.

z2=(y2)2

Multiply the exponents in (z12)2.

Apply the power rule and multiply exponents, (am)n=amn.

z12⋅2=(y2)2

Cancel the common factor of 2.

Cancel the common factor.

z12⋅2=(y2)2

Rewrite the expression.

z1=(y2)2

z1=(y2)2

z1=(y2)2

Simplify.

z=(y2)2

Apply the product rule to y2.

z=y222

Raise 2 to the power of 2.

z=y24

z=y24

Solve for z y=2 square root of z